Farmers Entrepreneurship and Performance of Red Onion Farming in Bantul District - Ulfah Nurdiani (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2015)
The purposes of this study were: (1) To identify the level of onion farmers entrepreneurship in Bantul district, (2) To determine the influence of individual factors, physical, social, economic and institutional environment on the level of farmers entrepreneurship and performance of red onion farming in Bantul district, and (3) To determine the effect of the level farmers entrepreneurship on performance of red onion farming in Bantul district. The method study uses descriptive analytical, which analyzed the data further to find a relationship or ratio between the variables in the theoretical framework of thinking. Data collection using questionnaires previously tested the validity of using Product Moment Correlation and reliability testing using Cronbach Alpha coefficients. Data analysis techniques broadly consists of three stages: a preliminary analysis to calculate individual farm performance indicators (produtifitas, revenue and Private Cost Ratio), descriptive analysis of the percentage of the study variables and analysis of structural equation model (SEM). The research results showed that the level of red onion farmers entrepreneurship in Bantul categorized high with an overall average percentage of 70.87%. Individual factors, physical, social, economic and institutional environment positive and significant impact on the farmers entrepreneurship and performance of farming. The factor that has the greatest positive effect of individual factors followed by the institutional environment. The physical environment and the economy have the same magnitude, while the smallest is the social environment influences. Farmer entrepreneurship positive effect on farm performance and has an important role in mediating the influence of individual and environmental factors on farm performance. These results provide evidence for the idea that entrepreneurial farmers is something that can be grown and can be considered to be a new approach in improving farm performance